Topografernes natur - Mellemgaard, Signe (Tidsskrift for kulturforskning, 2020)
Between 1750 and 1820, the topographical genre in Scandinavia changed to a significant orientation towards a thorough and systematic account of local natural resources, described through a natural history resting on classification. In fact, natural history became the very scheme or plan for the description of the location. This article looks at the notion of nature in these ’physical-economic’ treatises between 1750 and 1820. Moreover, it looks at the way natural history became the very model or method for the topographies in the form of a ’classical episteme’ as described by M. Foucault in The Order of Things, establishing knowledge as the arrangement of things in tables and systems of identity and difference. This is visible in the treatment of nature in the topographies but is also evident when it comes to the descriptions of the living conditions and the manner of living of the local population. The topographies, however, also have gaps and fissures that give way to the author’s natural history practices, their scientific uncertainties and their sensibilities towards nature. It sometimes seems to happen inadvertently, sometimes to be actively used to raise the interest and engagement of the reader in local nature.